Sustainable biopolymers for environmental friendly packaging materials - Ali, Fathilah; Awale, Raina Jama; Mohamad, Nur Lisa Farhana; Ismail, Norshafiq (2016)
Petroleum based packaging materials creates a waste disposal problem due to the nature of their degradation (them being nonbiodegradable). Polylactic acid (PLA) is a thermoplastic polymer derived from renewable resources with suitable biodegradation rate and properties comparable to conventional plastics. This study aims to improve the general properties of PLA and to reduce the cost of PLA-based products by producing blends, filler-reinforced composites and polyurethane.